2019
DOI: 10.1021/acsmacrolett.8b00987
|View full text |Cite
|
Sign up to set email alerts
|

How to Force Polymer Gels to Show Volume Phase Transitions

Abstract: Relatively few polymer gels are known to show volume phase transition where the gels undergo an abrupt change in the degree of swelling by passing through a three-phase equilibrium. Characteristic for such transition is the existence of van der Waals (vdW) loop on the dependence of solvent chemical potential versus polymer concentration. For the χ-induced transition, the existence of vdW loop is determined by the concentration dependence of the interaction function. It is shown that expansive mechanical strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…It would also be interesting to extend our model to other geometries, in particular, to look at the core-shell structure that forms in spherical beads, and the impact of expansive stresses on the core [15]. In two-and three-dimensional situations involving a gel that is thin compared to its length h L 0 , we expect additional instabilities to affect, for example, the transition fronts induced by the forced influx of solvent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It would also be interesting to extend our model to other geometries, in particular, to look at the core-shell structure that forms in spherical beads, and the impact of expansive stresses on the core [15]. In two-and three-dimensional situations involving a gel that is thin compared to its length h L 0 , we expect additional instabilities to affect, for example, the transition fronts induced by the forced influx of solvent.…”
Section: Discussionmentioning
confidence: 99%
“…A composition-dependent quadratic form of χ for PHEMA-water gels is given in Ref. [15] and varies between 0.4 and 1.3. The temperature and concentration dependence of χ for PNIPAM-water has been measured in Ref.…”
Section: Numerical Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For cross-linked systems, it has been suggested that the combinatorial part of refers to the loss of entropy due to coupling of segments into clusters of functionality f [ 41 , 42 , 43 ] because there is no logical reason to reduce for networks to solutions of linear polymers of infinite molecular weight. Within this concept, the extensive form of for Flory–Huggins lattice model reads where subscript n denotes a network, is number of moles of solvent, and are volume fractions of solvent and polymer, respectively, is the cycle rank of elastically active network chains, EANCs; it holds where f e is the number–average number of EANCs issuing from an elastically active crosslink, is the number of elastically active chains; is the interaction function.…”
Section: The Mixing Contributionmentioning
confidence: 99%
“…One of such equations was used for the analysis of the effect of strain in ref. [ 43 ] and a choice of them can be found in ref. [ 41 ].…”
Section: The Elastic Contribution and Swelling Change Of The Chemimentioning
confidence: 99%